PENGARUH TEMPERATUR AKTIVASI FISIKA TERHADAP KINERJA SUPERKAKASITOR BERBASIS ELEKTRODA KARBON DARI AMPAS SAGU - Erman Taer; Zikri Alrifani; Rika Taslim (Komunikasi Fisika Indonesia, 2018)
The manufacture of activated carbon based on sago pulp as a super-capacitor cell electrode has been successfully performed. Preparation of activated carbon begins with heating of drying raw materials in the sun and followed by oven drying, pre-carbonization, milling, sieving, chemical activation with 2 M concentration KOH solution, pellet printing, carbonization at 600° C using N2 gas followed by physics activation with temperature variation of 700° C; 750° C; 800° C; 850° C; 900° C using water vapor and polishing of pellets are some of the steps that are followed. Carbon electrode density values for each sample of AC 700, AC 750, AC 800, AC 850, and AC 900 are 0,790 g/cm3, 0,791 g/cm3, 0,795 g/cm3, 0,760 g/cm3, dan 0,754 g/cm3. The SEM results show the shape of the particles formed unoccupied. EDX test results show the percentage of carbon reaches 90.13%. The measurement of electrochemical properties performed by cyclic voltammetry method yielded an optimum specific capacitance of 106 F/g  obtained at a temperature of 750° C.